A simple and robust MPM framework for modelling granular flows over complex terrains. (September 2022) - Lei, Xiaoqin; Chen, Xiaoqing; Yang, Zongji; He, Siming; Zhu, Lei; Liang, Heng
Abstract: Many geo-hazards phenomena are characterized by granular flows over complex natural terrains, which are challenging to be simulated numerically. In this paper, we propose a simple yet robust modelling framework for such phenomena based on the Material Point Method (MPM). Within the framework, the complex terrain is represented by a serial of fixed rigid material points constructed from the basal surface's Digital Terrain Model (DTM); a novel multi-material contact model with accurate surface normal vectors is then developed to handle interactions between the rigid terrain and the non-rigid sliding material. Detailed procedure for implementing the proposed DTM-based contact modelling framework is presented. The proposed approach is validated both analytically and experimentally through two benchmark examples. Then the dynamic process of a realistic landside is simulated to demonstrate the robustness of the proposed MPM framework. It is shown that our DTM-based framework can effectively mitigate the notorious step-wise boundary effect associated with conventional MPM contact algorithms and suitable for modelling granular flows over complex terrains.